PERAKTIK GADAI SAWAH TANPA BATAS WAKTU - Arfah, Arfah; Payung, Otniel (Jurnal Delik ADPERTISI, 2024)
The main problem of this research is how the practice of pawning rice fields indefinitely in the new Maros sub-district, Maros Regency, namely debtors who pawn their rice fields to creditors who will provide money loans. Then the rice fields change hands to the creditor or debtor. As long as it is in the hands of the creditor, the right to cultivate, plant and harvest the rice fields is in the hands of the creditor and there is no time limit for the repayment of the loan. This can certainly harm one of the parties, usually the party who feels the most disadvantaged is the pawnbroker (Debtor), because the rice fields that are used as collateral are fully utilized by the pawnbroker. This type of research is field research carried out in Maros Baru District, Maros Regency. To obtain valid data, the compiler used several data collection methods, namely interviews and documentation. There are two sources of data in this study, namely primary data sources as a result of interviews with sub-district officials, pawnbrokers and pawnbrokers, while secondary data is in the form of documents, books, records and so on. The analysis of the collected data uses a descriptive method of analysis using a qualitative approach. Based on the results of the research, it was concluded that in the practice of pawning rice fields carried out by the people of Maros Baru sub-district, Maros regency, there are two first, the intention is indeed to help and the second is only to take advantage of what the debtor is exclaiming.